Hyaluronic acid fillers with cohesive polydensified matrix for soft-tissue augmentation and rejuvenation: a literature review - Prasetyo AD; Prager W; Rubin MG; Moretti EA; Nikolis A (Dove Medical Press, 2016)
Adri D Prasetyo,1 Welf Prager,2 Mark G Rubin,3 Ernesto A Moretti,4 Andreas Nikolis5 1Rejuva Skin & Beauty, Surabaya, Indonesia; 2Prager & Partner, Hamburg, Germany; 3University of California, San Diego, CA, USA; 4Gamma Health Group, Sanatorio Los Arroyos, Santa Fe, Republic of Argentina; 5Victoria Park Clinical Research Centre, Westmount, QC, Canada Background: Cohesive monophasic polydensified fillers show unique viscoelastic properties and variable density of hyaluronic acid, allowing for a homogeneous tissue integration and distribution of the material.Objective: The aim of this paper was to review the clinical data regarding the performance, tolerability, and safety of the Belotero® fillers for soft-tissue augmentation and rejuvenation.Methods: A literature search was performed up until May 31, 2015 to identify all relevant articles on Belotero® fillers (Basic/Balance, Hydro, Soft, Intense, Volume) and equivalent products (Esthélis®, Mesolis®, Fortélis®, Modélis®).Results: This comprehensive review included 26 papers. Findings from three randomized controlled trials showed a greater reduction in nasolabial fold severity with Belotero® Basic/Balance than with collagen (at 8, 12, 16, and 24 weeks, n=118) and Restylane® (at 4 weeks, n=40), and higher patient satisfaction with Belotero® Intense than with Perlane® (at 2 weeks, n=20). With Belotero® Basic/Balance, an improvement of at least 1 point on the severity scale can be expected in ~80% of patients 1–6 months after injection, with an effect still visible at 8–12 months. Positive findings were also reported with Belotero® Volume (no reduction in hyaluronic acid volume at 12 months, as demonstrated by magnetic resonance imaging), Soft (improvement in the esthetic outcomes when used in a sequential approach), and Hydro (improvement in skin appearance in all patients). The most common adverse effects were mild-to-moderate erythema, edema, and hematoma, most of which were temporary. There were no reports of Tyndall effect, nodules, granulomas, or tissue necrosis.Conclusion: Clinical evidence indicates sustainable esthetic effects, good safety profile, and long-term tolerability of the Belotero® fillers, particularly Belotero® Basic/Balance and Intense. Keywords: CPM®, dermal filler, facial lines, filling, nasolabial fold, wrinkle